A Clustering Routing Algorithm Based Ant Colony Optimization for Wireless Sensor Network - Yang, Xiong; Jin, Zhi Gang; Chen, Xian Yi (Applied Mechanics and Materials, 2012)
As ant colony optimization algorithm and clustering routing algorithm were discussed deeply, a clustering routing algorithm based ant colony optimization (CRAACO) for wireless sensor networks has been put forward. To test the performance of CRAACO, simulations have been done from information fusion rates, remaining energy and network lifetime. The experiment results show that the CRAACO can work effectively and may be used in wireless sensor networks.